Ритмічна організація мовлення: когнітивний аспект - Забужанська, Інна Дем’янівна; Zabuzhanska, I. D. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті представлено підходи вітчизняних і зарубіжних учених із галузей філології, психології, психопоетики, когнітивної поетики та нейронаук щодо ритмічної організації мовлення. Висвітлено й обґрунтовано наявність зв’язку між ритмічною організацією поетичного мовлення та когнітивними процесами мовця в процесі породження і смислосприйняття тексту. Важливим є окреслення перспектив подальших теоретико-методологічних пошуків дослідження ритму в площині когнітивної лінгвістики. The research is of an interdisciplinary nature. The article presents the approaches of local and foreign scholars from the branches of philology, psychology, cognitive poetics and neurosciences on the specifics of the correlation of the rhythmic organization of poetic speech with the cognitive processes of the speaker. It brings some of the results of the study of psychopoetics on the given problem.The need to integrate the methods of cognitive linguistics and experimental phonetic research methods of the rhythmic parameters of English poetry is revealed and substantiated. This paper also puts forward the issue of the specificity of rhythm-intonation organization of poetic speech on the material of English poetic texts in the light of linguistic and cognitive research; the perspectives of further theoretical and methodological research in the plane of cognitive linguistics are outlined. Experimental phonetic research is suggested to be taken into account in this respect.
Rhythmic Organization of Speech: the Cognitive Aspect
Keywords: ритм; rhythm; поетичне мовлення; poetic speech; ритмічна організація rhythmic; organization